Protection of stromal cell-derived factor-1 SDF-1/CXCL12 against proteases yields improved skin wound healing - Pereira, Rafaela Vaz Sousa; EzEldeen, Mostafa; Ugarte-Berzal, Estefania; Vandooren, Jennifer; Martens, Erik; Gouwy, Mieke; Ganseman, Eva; Van Damme, Jo; Matthys, Patrick; Vranckx, Jan Jeroen; Proost, Paul; Opdenakker, Ghislain (Frontiers in Immunology, 2024)
SDF-1/CXCL12 is a unique chemotactic factor with multiple functions on various types of precursor cells, all carrying the cognate receptor CXCR4. Whereas individual biological functions of SDF-1/CXCL12 have been well documented, practical applications in medicine are insufficiently studied. This is explained by the complex multifunctional biology of SDF-1 with systemic and local effects, critical dependence of SDF-1 activity on aminoterminal proteolytic processing and limited knowledge of applicable modulators of its activity. We here present new insights into modulation of SDF-1 activity in vitro and in vivo by a macromolecular compound, chlorite-oxidized oxyamylose (COAM). COAM prevented the proteolytic inactivation of SDF-1 by two inflammation-associated proteases: matrix metalloproteinase-9/MMP-9 and dipeptidylpeptidase IV/DPPIV/CD26. The inhibition of proteolytic inactivation was functionally measured by receptor-mediated effects, including intracellular calcium mobilization, ERK1/2 phosphorylation, receptor internalization and chemotaxis of CXCR4-positive cells. Protection of SDF-1/CXCL12 against proteolysis was dependent on electrostatic COAM-SDF-1 interactions. By in vivo experiments in mice, we showed that the combination of COAM with SDF-1 delivered through physiological fibrin hydrogel had beneficial effect for the healing of skin wounds. Collectively, we show that COAM protects SDF-1 from proteolytic inactivation, maintaining SDF-1 biological activities. Thus, protection from proteolysis by COAM represents a therapeutic strategy to prolong SDF-1 bioavailability for wound healing applications.